Kesha’s Comeback and the Stakes of Live Performance: Connecting through Trauma at the 2018 Grammy Awards - Hearfield, Katelyn (Journal of Musicological Research, 2021)
The use of live popular music performance as a platform to address gendered and sexual violence and trauma within the popular music industry can be demonstrated through the analysis of Kesha’s performance of “Praying” at the 2018 Grammy Awards. Analyzing the artist’s vocal and artistic delivery, in addition to her public persona following her allegations of sexual abuse against producer Lukasz Gottwald (Dr. Luke), illustrates how live performance—building on and contrasting with social media campaigns, such as #FreeKesha and #MeToo, and studio recordings—is a uniquely effective mode of processing individual and collective trauma.
Keywords: Bibliographie; Nettoyer